Assessing the Impact of Financial Inclusion Programs on Rural Commerce in India (International Journal of Food and Nutritional Sciences, 2023)
This paper evaluates the effects of the external financial enhancements on rural trade in India, emphasizing on how such programs affect small business, farmers, and other entrepreneurs in the rural areas. The government’s twin goals for financial inclusion through ‘.paymentization’ of Indians, especially the unbanked rural poor through successful initiatives like Pradhan Mantri Jan Dhan Yojana (PMJDY), MUDRA and the financial Literacy Campaigns. These programs aim at facilitating credit, savings, insurance, as well as, digital banking services with an endeavor of betterment of the living standards of the villagers and boosting for the economic development of the region. This paper assesses the impact of these initiatives by administering a questionnaire to rural business owners and players that looks at how improved access to financial services shapes their business management, expansion and viability. It also assesses factors like, digital literacy which may limit effective usage, infrastructure constraints that prevent access to essential services, availability of complementary credit facilities, among others, which may hamper achievement of the goal of ‘financial inclusion’. The study highlights the gain in uptake of commerce in rural areas through implementation of financial inclusion but shows the level awareness, access and facility which requires improvement to for optimum utilization of such programmes. This paper contributes knowledge on the effectiveness of financial inclusion in achieving sustainable economic development in rural areas of India and provide policy recommendations for increasing the outreach and effectiveness of financial inclusion to rural areas.